VARIASI BERAT JENIS GELAM BERDASARKAN LOKASI TUMBUH DAN TINGKAT PERTUMBUHAN (Specific Gravity Variation of Melaleuca sp. According Its Site Location and Growth Level): Alpian, Wahyu Supriyati, M. Damiri, Christopheros - Admin JHT (Jurnal Hutan Tropika, 2015)
ABSTRACTGelam (Melaleuca sp.) mostly grew at the degraded peat-swamp forest. This study investigated the specific gravity of gelam based on two factors, i.e. site location and growth level. Site location was divided into two sub factors of peat thickness namely 51 to 100 cm (l1) and 101 to 200 cm (l2). Growth level was divided into four stages namely seedling, sapling, poles, and tree. Research result show that specific gravity of gelam wood (dry-air and dry-kiln) at the l2 was bigger than l1. Specific gravity of gelam wood (dry-air and dry-kiln) based on the growth level at the location 1 and location 2 show the same pattern, namely the level of tree > pole > sapling > seedling. The interaction between location versus growth level are no significant different on the specific gravity of the gelam wood, and it is start from 0.55 to 0.77 or at the medium category.Keywords: Gelam, growth level, site location, specific gravity